2021
DOI: 10.1002/lpor.202100028
|View full text |Cite
|
Sign up to set email alerts
|

Low Threshold Room Temperature Polariton Lasing from Fluorene‐Based Oligomers

Abstract: Organic semiconductors possessing tightly bound Frenkel excitons are known to be attractive candidates for demonstrating polariton lasing at room temperature. As polariton lasing can occur without inversion, it is a potential route to very low threshold coherent light sources. However, so far, the thresholds of organic polariton lasers have generally been much higher than those of organic photon lasers. Here this problem has been addressed by investigating two new organic molecules with a structure combining f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Polariton lasing was thus envisioned with intriguing characteristics and closely related to BEC [116] . An attractive feature of polariton lasers is that they can operate with significantly lower thresholds compared to their photonic counterparts [35,[117][118][119][120] .…”
Section: Polariton Lasermentioning
confidence: 99%
“…Polariton lasing was thus envisioned with intriguing characteristics and closely related to BEC [116] . An attractive feature of polariton lasers is that they can operate with significantly lower thresholds compared to their photonic counterparts [35,[117][118][119][120] .…”
Section: Polariton Lasermentioning
confidence: 99%
“…[47,48] Samuel et al have recently demonstrated room temperature polariton lasing with lowest reported thresholds in organic semiconductor molecules of fluorene-based oligomers. [49] Since polariton lasing does not involve energy-level systems, this type of laser will not be discussed here.…”
Section: General Excited-state Process For Organic Lasersmentioning
confidence: 99%
“…Polariton formation has been demonstrated in various materials, e.g., inorganic semiconductors, and Rydberg atoms , at low temperatures. Room-temperature polaritons have been observed experimentally in organic materials, followed by the emergence of unusual phenomena such as the formation of polaritonic Bose–Einstein condensates at room temperature, , polariton lasing, and ultra-long-range energy transport. The reason behind the formation of stable room-temperature polaritons in organics is their low dielectric constants, which give rise to the formation of bound electron–hole pairs with a large binding energy, on the order of 0.5–1 eV. In addition, organic dyes also possess large transition dipole moments, which enhances the light–matter interaction.…”
Section: Introductionmentioning
confidence: 99%